2011
DOI: 10.5194/os-7-305-2011
|View full text |Cite
|
Sign up to set email alerts
|

On the freshening of the northwestern Weddell Sea continental shelf

Abstract: Abstract. We analyzed hydrographic data from the northwestern Weddell Sea continental shelf of the three austral winters 1989, 1997, and 2006 and two summers following the last winter cruise. During summer a thermal front exists at ∼64 • S separating cold southern waters from warm northern waters that have similar characteristics as the deep waters of the central basin of the Bransfield Strait. In winter, the whole continental shelf exhibits southern characteristics with high Neon (Ne) concentrations, indicat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
51
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(57 citation statements)
references
References 41 publications
5
51
1
Order By: Relevance
“…The ocean reanalyses that showed a warming trend (MyOcean and SODA) also presented an increase in salinity, while ECMWF showed cooling and freshening trends (Table 4). A freshening trend of the WSBW would be expected as a result of shelf water freshening (e.g., Hellmer et al, 2011;Azaneu et al, 2013) because this bottom water results from shelf water mixing. However, clear salinity changes have not yet been observed in the deep layers of the Weddell Sea (Azaneu et al, 2013); the causes are not yet clearly identified but could be the result of the opposing effects of source waters and dynamic processes masking signal identification.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ocean reanalyses that showed a warming trend (MyOcean and SODA) also presented an increase in salinity, while ECMWF showed cooling and freshening trends (Table 4). A freshening trend of the WSBW would be expected as a result of shelf water freshening (e.g., Hellmer et al, 2011;Azaneu et al, 2013) because this bottom water results from shelf water mixing. However, clear salinity changes have not yet been observed in the deep layers of the Weddell Sea (Azaneu et al, 2013); the causes are not yet clearly identified but could be the result of the opposing effects of source waters and dynamic processes masking signal identification.…”
Section: Discussionmentioning
confidence: 99%
“…Over the past few decades, changes in the thermohaline properties of AABW source waters have been reported, such as freshening of the dense waters in the shelf regions (e.g., Hellmer et al, 2011;Azaneu et al, 2013) and long-term warming of WDW within the Weddell Sea (e.g., Robertson et al, 2002;Smedsrud, 2005). In turn, WSBW in the inner Weddell Sea also experienced warming during the second half of the 1990s (Fahrbach et al, 2004.…”
Section: T S Dotto Et Al: Weddell Sea Water Masses In Distinct Ocementioning
confidence: 99%
“…These collapses have reduced the restraint of the ice shelves on the flow of grounded tributary glaciers, causing them to accelerate Berthier et al, 2012) and thereby contributing to sea-level rise (Shepherd et al, 2012). Increased freshwater input to the ocean from the collapses and subsequent excess ice discharge may be implicated in the freshening of Antarctic Bottom Water formed nearby (Hellmer et al, 2011;Jullion et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Net precipitation is thought to be intensifying [17,18], although exact trends remain poorly constrained [19,20], while elevated glacial discharge into the region [21] has led to the freshening of both shelf waters [22] and bottom waters [23], primarily linked to increased ice-shelf calving and the speeding up of tributary glaciers in the vicinity of the Larsen ice shelves [24,25].…”
Section: Introductionmentioning
confidence: 99%